Trump, Snakes and the Power of Fables - Stevens, Katharina (Informal Logic, 2018)
At a recent rally, Donald Trump resumed a habit he had developed during his election-rallies and read out the lyrics to a song. It tells the Aesopian fable of The Farmer and the Snake: A half frozen snake is taken in by a kind-hearted person but bites them the moment it is revived. Trump tells the fable to make a point about Islamic immigrants and undocumented immigrants from Southern and Central America: He claims the immigrants will cause problems and much stricter immigration-policies are needed. I assume that Trump treats the fable as an argumentative device for supporting his stance on immigration. He uses it as a source-analogue both for the conclusion that immigrants will cause problems and for changing the frame in which immigrants and those willing to let them enter are seen. This gives me opportunity to examine the effect fables have as argumentative devices. Fables are a popular and effective choice for political argumentation. They are slimmed down, semi-abstract narratives, well suited for directing the audience's attention to a few properties of an otherwise complex situation. However, this also makes it easy to use them for manipulating an audience into oversimplifying complex contexts and stereotyping human beings.